2020
DOI: 10.1186/s12348-020-00228-w
|View full text |Cite
|
Sign up to set email alerts
|

Current diagnostic tools and management modalities of Nocardia keratitis

Abstract: Nocardia species are an uncommon but important cause of keratitis. The purpose of this review is to discus previous published papers relation to the epidemiology, etiology, diagnosis and management of Nocardia keratitis. Nocardia asteroides is the most frequently reported from Nocardia keratitis. Pain, photophobia, blepharospasm and lid swelling are mainly clinical manifestations. Usual risk factors for Nocardia keratitis are trauma, surgery, corticosteroids, and contact lens wear. Several antibiotics were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…The diagnosis of corneal ulcer caused by Nocardia spp. is often misdiagnosed and delayed, resulting in inappropriate treatment and complications [5]. However, in the present case, we diagnosed the Gram staining and weak acid-fast bacilli on the first day of staining.…”
Section: Discussionmentioning
confidence: 57%
See 2 more Smart Citations
“…The diagnosis of corneal ulcer caused by Nocardia spp. is often misdiagnosed and delayed, resulting in inappropriate treatment and complications [5]. However, in the present case, we diagnosed the Gram staining and weak acid-fast bacilli on the first day of staining.…”
Section: Discussionmentioning
confidence: 57%
“…The fullthickness infiltrates wreath patterns with a persistent epithelial defect with white stromal opacities. The wreath pattern suggests a Nocardial infection of the corneal [4]. The diagnosis of corneal ulcer caused by Nocardia spp.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Amikacin is an aminoglycoside most commonly administered intravenously and intramuscularly, yet other routes are also utilized, such as intrathecal, intraventricular, topical, and inhaled 8 , 17 , 18 . In our quest to identify compounds that inhibit the AAC(6′)-Ib amikacin-disabling action, we recently found that various cations effectively interfere with the enzymatic inactivation 11 , 12 , 19 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Amikacin is an aminoglycoside most commonly administered intravenously and intramuscularly, yet other routes are also utilized, such as intrathecal, intraventricular, topical, and inhaled 8,17,18 . In our quest to identify compounds that inhibit the AAC(6′)-Ib amikacin-disabling action, we recently found that various cations effectively interfere with the enzymatic inactivation 11,12,[19][20][21] .…”
Section: Discussionmentioning
confidence: 99%